2020
DOI: 10.1021/acs.energyfuels.0c02656
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Interfacial Material in Asphaltenes Responsible for Oil/Water Emulsion Stability

Abstract: This study aimed at a better understanding of the structure and properties of the most interfacially active asphaltenes responsible for the stability of oil/water emulsions. Interfacial material (IM) was extracted from three different crude oils using a modified solvent washing procedure. Structural parameters of IM were analyzed and compared to those of a parent asphaltene. High-resolution microscopy imaging was performed to correlate IM microstructure to their interfacial properties. Although IM and asphalte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
71
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(72 citation statements)
references
References 47 publications
1
71
0
Order By: Relevance
“…However, after the heating reaction (Figure b), the Raman spectra of nanoparticles became significantly different. Besides the sharp G peak at 1580 cm –1 , a relatively broad D peak at 1350 cm –1 was observed for the CuO nanoparticles, which represents an ordered molecular boundary structure . A very weak G′ (or 2D) peak at 2700 cm –1 was also found for CuO nanoparticles, indicating a multilayer structure of graphene.…”
Section: Results and Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…However, after the heating reaction (Figure b), the Raman spectra of nanoparticles became significantly different. Besides the sharp G peak at 1580 cm –1 , a relatively broad D peak at 1350 cm –1 was observed for the CuO nanoparticles, which represents an ordered molecular boundary structure . A very weak G′ (or 2D) peak at 2700 cm –1 was also found for CuO nanoparticles, indicating a multilayer structure of graphene.…”
Section: Results and Discussionmentioning
confidence: 88%
“…The asphaltenes were recovered from the filter cake by dissolution in toluene and then dried after solvent evaporation. The elemental composition of the asphaltene is shown in Table …”
Section: Methodsmentioning
confidence: 99%
“…The carbon, hydrogen, nitrogen, sulfur, and oxygen (CHNS/O) contents were analyzed using a FlashSmart elemental analyzer (Thermo Scientific, USA) using two reactor columns, a thermal conductivity detector, and appropriate calibration standards. More details of these experimental procedures can be found elsewhere …”
Section: Methodsmentioning
confidence: 99%
“…Significant progress has been made over the past decade to isolate and characterize the interfacial material (IM) responsible for the stability of o/w emulsions. Centrifugation studies revealed that the IM may constitute less than 2 wt % of the total asphaltenes present in oil or bitumen. , Asphaltenes are a polydisperse mixture of the heaviest and most polarizable fraction of crude oil and contain thousands of molecules with different structures . Even though IM species are a subfraction of asphaltenes, their concentration is so low that they do not affect the average properties of asphaltenes in bulk solution.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation